Systematic Review: Potential of Garlic Extract (Allium Sativum) as a Treatment for Diarrhea (E. Coli) - R Mohamad Javier; Laksmitha Saktiono Safitri; Lillya Yasmine Nur Baiti; Prima Sultan Hudiyanto; Irma Suswati; Hawin Nurdiana; Djoni Djunaedi (PT FORMOSA CENDEKIA GLOBAL, 2023)
Diarrheal disease continues to be one of the major public health problems worldwide, with more than 1.5 million deaths each year and most of them in children under 5 years of age. The incidence of diarrheal diseases averages 2-3 episodes per child per year. Excessive use of antibiotics as antidiarrheals is associated with an increase in bacterial resistance to antibiotics, medical costs, and the incidence of side effects. In past research, it has been found that garlic has a wide antimicrobial spectrum so that it can kill gram-negative and gram-positive bacteria, so it can be used as an alternative treatment for diarrhea. The purpose of carrying out this study was to describe the potential for garlic extract that have an effect on gram-negative bacteria that cause diarrhea, this natural ingredient can be used as a safe alternative treatment to treat infectious diseases that cause gram-negative bacterial diarrhea. This research method is Narrative review (Literature review). In a journal that discusses the effectiveness of garlic as an antimicrobial regarding the antibacterial activity of thiosulfinates using the petri plate diffusion test, the efficacy of the substances cannot be compared with each other because the assumed diffusion rates are different. In the journal on Comparison of the antibacterial activity of thiosulfinates using the petri plate diffusion test, the efficacy of the substances cannot be compared with each other because the assumed diffusion rates are different. The results showed that the MIC and MBC results of each bacteria given garlic extract were different, even though they were both gram-negative bacteria. Garlic extract has the highest effectiveness on E. coli bacteria based on in vitro studies conducted, compared to Salmonella, Shigella, V. cholerae bacteria according to the characteristics of these bacteria